2020
DOI: 10.1002/vjch.201900082
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents from ethyl acetate extract of the stems of Rourea oligophlebia Merr.

Abstract: Rourea oligophlebia (Connaraceae) plant has been traditionally used for the treatment of bleeding and bone fractures. Chemical study on the ethyl acetate extract of the stem of Rourea oligophlebia, collected at Ben En National Park, Thanh Hoa province, have led to the isolation of five compounds including friedelin (1), friedelinol (2), coniferyl alcohol (3), 7α‐hydroxyl‐3β‐sistosterol (4) and scopoletin (5). The structures of these compounds have been elucidated by NMR, MS spectroscopic data and comparison wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In addition, the genus Rourea is also commonly used in traditional medicine such as R. regusa root for respiratory diseases, R. concolor for kidney disease, and R. mimosoides for bloody diarrhea treatments [10] . Previous studies indicated that the secondary metabolites from R. oligophlebia have antibacterial and cytotoxic properties [9,11] . These results may assist in prescribing oriental traditional medicine, although there is no further scientific evidence from this species.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…In addition, the genus Rourea is also commonly used in traditional medicine such as R. regusa root for respiratory diseases, R. concolor for kidney disease, and R. mimosoides for bloody diarrhea treatments [10] . Previous studies indicated that the secondary metabolites from R. oligophlebia have antibacterial and cytotoxic properties [9,11] . These results may assist in prescribing oriental traditional medicine, although there is no further scientific evidence from this species.…”
Section: Introductionmentioning
confidence: 96%
“…[10] Previous studies indicated that the secondary metabolites from R. oligophlebia have antibacterial and cytotoxic properties. [9,11] These results may assist in prescribing oriental traditional medicine, although there is no further scientific evidence from this species. In this study, the in vitro antioxidant, anti-skin-aging, anti-inflammatory, and anti-acetylcholine activities of n-hex, AcOEt, BuOH, MeOH, and aqueous extracts from R. oligophlebia roots were investigated for the first time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations